Crystal structure and Hirshfeld surface analyses, intermolecular interaction energies and energy frameworks of methyl 6-amino-5-cyano-2-(2-methoxy-2-oxoethyl)-4-(4-nitrophenyl)-4H-pyran-3-carboxylate - Farid N. Naghiyev; Tuncer Hökelek; Victor N. Khrustalev; Huseyn M. Mamedov; Alebel N. Belay; Jamshid Ashurov; Ibrahim G. Mamedov (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, C17H15N3O7, contains pyran and phenyl rings, with the pyran ring exhibiting a flattened-boat conformation. In the crystal, intermolecular N—H...N hydrogen bonds link the molecules into centrosymmetric dimers, forming R22(12) ring motifs. These dimers are linked through N—H...O hydrogen bonds into a three-dimensional architecture. A Hirshfeld surface analysis indicates that the most important contributions for the crystal packing are from H...O/O...H (29.7%), H...H (28.7%), H...C/C...H (16.0%) and H...N/N...H (12.9%) interactions. In addition to van der Waals interactions and N—H...N and N—H...O hydrogen bonds, halogen bonds, tetrel bonds and pnictogen bonds also play an important role in the cohesion of the crystal structure.